To solve this system of equations, we can use the method of substitution or elimination. Here, we will use the method of elimination.
First, let's multiply the second equation by 3 to make the coefficients of x the same as in the first equation:
-5x + 2y = 13
Multiply by 3:
-15x + 6y = 39
Now, the system becomes:
3x + 6y = 21
-15x + 6y = 39
Next, let's add the two equations together to eliminate y:
3x + 6y - 15x + 6y = 21 + 39
-12x = 60
x = -5
Now that we have the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the first equation:
3(-5) + 6y = 21
-15 + 6y = 21
6y = 36
y = 6
Therefore, the solution to the system of equations is (-5, 6).
Solve the system of equations.%0D%0A3x+6y=21%0D%0A–5x+2y=13(1 point)%0D%0A(, )
5 answers
please do it one more time without giving the same answer -5,6
Let's solve the system of equations using the elimination method with a different result:
3x + 6y = 21 (Equation 1)
-5x + 2y = 13 (Equation 2)
First, let's multiply Equation 1 by 5 and Equation 2 by 3 to make the coefficients of y the same:
15x + 30y = 105 (Equation 1 multiplied by 5)
-15x + 6y = 39 (Equation 2 multiplied by 3)
Now, let's add both equations together to eliminate x:
15x + 30y + (-15x + 6y) = 105 + 39
36y = 144
y = 4
Now that we have the value of y, we can substitute it back into one of the original equations to solve for x. Let's use Equation 1:
3x + 6(4) = 21
3x + 24 = 21
3x = -3
x = -1
Therefore, the solution to the system of equations is (-1, 4).
3x + 6y = 21 (Equation 1)
-5x + 2y = 13 (Equation 2)
First, let's multiply Equation 1 by 5 and Equation 2 by 3 to make the coefficients of y the same:
15x + 30y = 105 (Equation 1 multiplied by 5)
-15x + 6y = 39 (Equation 2 multiplied by 3)
Now, let's add both equations together to eliminate x:
15x + 30y + (-15x + 6y) = 105 + 39
36y = 144
y = 4
Now that we have the value of y, we can substitute it back into one of the original equations to solve for x. Let's use Equation 1:
3x + 6(4) = 21
3x + 24 = 21
3x = -3
x = -1
Therefore, the solution to the system of equations is (-1, 4).
correct thank you
You're welcome! If you have any more questions or need further assistance, feel free to ask. I'm here to help!